2017
DOI: 10.1136/bmjopen-2016-015141
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physician burnout and quality of healthcare in terms of safety and acceptability: a systematic review

Abstract: ObjectivesThis study reviews the current state of the published peer-reviewed literature related to physician burnout and two quality of care dimensions. The purpose of this systematic literature review is to address the question, ‘How does physician burnout affect the quality of healthcare related to the dimensions of acceptability and safety?’DesignUsing a multiphase screening process, this systematic literature review is based on publically available peer-reviewed studies published between 2002 and 2017. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
269
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(292 citation statements)
references
References 61 publications
9
269
2
12
Order By: Relevance
“…Medical error is the third leading overall cause of death in the United States . There is growing evidence to support the link between medical errors and physician burnout . The largest prospective study of the impact of burnout on patient safety in the United States surveyed 24,922 American College of Surgeons members, of whom 7,905 responded.…”
Section: The Impact Of Physician Burnout On Medical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Medical error is the third leading overall cause of death in the United States . There is growing evidence to support the link between medical errors and physician burnout . The largest prospective study of the impact of burnout on patient safety in the United States surveyed 24,922 American College of Surgeons members, of whom 7,905 responded.…”
Section: The Impact Of Physician Burnout On Medical Practicementioning
confidence: 99%
“…11 There is growing evidence to support the link between medical errors and physician burnout. [12][13][14] The largest prospective study of the impact of burnout on patient safety in the United States surveyed 24,922 American College of Surgeons members, of whom 7,905 responded. The study found that higher levels of burnout are associated with an increased likelihood of reporting an error in the last 3 months, and burnout and depression were among the strongest risk factors for error after adjusting for hours worked and number of calls per week.…”
Section: Patient Safetymentioning
confidence: 99%
“…In addition to the negative clinical impacts on individuals, burnout negatively affects workplace organizations. In general, burnout among health care providers has been linked to increased absenteeism and attrition, as well as reduced quality of care and more frequent medical errors, potentially compromising patient safety …”
Section: Introductionmentioning
confidence: 99%
“…In general, burnout among health care providers has been linked to increased absenteeism and attrition, as well as reduced quality of care and more frequent medical errors, potentially compromising patient safety. [6][7][8][9] According to the Job Demands-Resources Theory, burnout most often results from a prolonged, ongoing imbalance between work demands and job-related resources, whereby work demands significantly exceed job-related resources. 10 Job demands are defined as physical, social, or organizational aspects that require sustained physical or mental effort (eg, physical workload, time pressure, physical environment).…”
Section: Introductionmentioning
confidence: 99%
“…These are catastrophic findings for the public as well as for the individual physicians, and rationing through inconvenience is part of the problem. The inconveniences create a minor irritant for patients but contribute to an epidemic of unhappiness, a reduction of clinical availability, and negative impacts on patient care when imposed on physicians …”
Section: Another Voicementioning
confidence: 99%